SOSIALISASI SERTIFIKASI â€œCLEANLINESS, HEALTH, SAFETY AND ENVIRONMENTâ€: BAGI STAKEHOLDER DESA WISATA SEKOTONG BARAT - I Nyoman Nugraha Ardana Putra; Hadi Mahmudi; Sujadi Sujadi; Rahman Rahman; Abdul Manan (Universitas Mataram, 2023)
Sekotong Barat Village has now been designated as a tourist village that has beautiful beaches and marine life and stores a million biota and mineral wealth in it. However, this area often experiences both natural and non-natural disasters. Of course this is a problem in the development of tourism in West Sekotong. The solution offered based on these problems is to conduct training and socialization on Cleanliness, Health, Safety and Environment (CHSE). The method used is the lecture on the awareness of village tourism stakeholders for CHSE socialization. The result is the development of a tourism village based on health protocols, so that the arrival of tourists to this village is a gift for tourism operators and at the same time protecting this area from the spread of the COVID-19 virus (non-natural disasters) and the comfort of not worrying about frequent natural disasters. happened because it was anticipated. The conclusion from the implementation of this activity is that tourism operators in West Sekotong are aware of the importance of certification and are immediately CHSE certified so as to increase the comfort of tourists in enjoying destinations.